Edukasi Pengaruh Pola Tidur terhadap Obesitas pada Remaja - Suryati, Suryati; Dormina, Dormina; Irwandi, Irwandi (Jurnal Abdimas Kesehatan (JAK), 2024)
Obesity is a problem of excess nutrition. 4.8% of Indonesian children have more nutritional status. Obesity in adolescents is a major concern because it will risk continuing into adulthood and have a long impact on health. Lack of sleep will disrupt the hormonal stability that regulates appetite, namely leptin & ghrelin. Lack of sleep can also trigger fatigue which will have an impact on reducing physical activity so that it can cause obesity. This activity aims to increase understanding and motivation for adolescents to prevent obesity. The expected goal of this activity is to increase teenagers' knowledge about the influence of sleep patterns on obesity. The activity method is to provide health education. The main target is teenagers at SMA Negeri 11 Muaro Jambi Regency. The results of the activity evaluation showed an increase in teenagers' knowledge before (45%) and after being given counseling (80%).. Along with the development of technology, children are now increasingly playing gadgets and watching television until late at night. The school is expected to play a role in providing education to all students about the importance of adequate sleep to prevent obesity in adolescents.